A panel of antibodies for the immunostaining of Bouin's fixed bone marrow trephine biopsies. Issue 6 (June 1997) - Gala, J L; Chenut, F; Hong, K B; Rodhain, J; Camby, P; Philippe, M; Scheiff, J M
Abstract : AIMS: To assess a panel of antibodies on Bouin's fixed bone marrow trephine (BMT) biopsies. These biopsies are widely used in routine diagnosis of various haematological malignancies and may be the sole material available in many centres; however, information regarding the immunostaining of this material is lacking. METHODS: Biopsies were taken from 72 patients presenting with various haematological malignancies (leukaemia, 38; lymphoma, 14; multiple myeloma, 20). A panel of antibodies was assessed on Bouin's fixed BMT biopsies by the alkaline phosphatase-antialkaline phosphatase method. RESULTS: Three B (MB2, LN-2, Ki-B5) and two T cell lineage antibodies (UCHL-1, CD3-r) reliably identified lymphoid cells, while MPO-r, Leu-M1/CD15, and KP-1/CD68 recognised cells from the myeloid or histiocytic/macrophage series. Reed-Sternberg cells were stained by LN-2, Leu-M1, and CD30. Antibodies specific for plasma cells (VS38) and hairy cells (DBA.44) gave a variable pattern of staining. Among the proliferation markers, proliferative cell nuclear antigen but not Ki-67 related antibodies were effective. CONCLUSION: This study presents a panel of antibodies with reactivity not restricted to common fixatives that are also suitable for Bouin's fixed BMT biopsies.